Penilaian Kinerja Keuangan terhadap Nilai Perusahaan BUMN Bidang Konstruksi yang Terdaftar di Bursa Efek Indonesia - Anggi Angga Resti (Journal of Management and Business Review, 2021)
This study aims to determine of the financial performance on firm value of state-owned construction companies listed in the Indonesia Stock Exchange for period 2016-2019 which based on Decree of the Minister of State-Owned Enterprises No: KEP-100/MBU/2002. Assessment of financial healthy used eight indicators, there are ROE (Return On Equity), ROI (Return On Investment), cash ratio, current ratio, collection periods, inventory turnover, total asset turn over, and total equity to total asset. The research is conducted in four constructions state-owned enterprises (SOE) listed in the Indonesia Stock Exchange for the period 2016-2019.The documents required are the annual financial statements of PT. Adhi Karya (Persero) Tbk., PT. Housing Development Tbk., PT. Waskita Karya (Persero) Tbk., and PT. Wijaya Karya (Persero) Tbk., for the period 2016-2019. Based on the results show assessment of the financial performance and firm value of state-owned companies in the construction sector listed on the Indonesia Stock Exchange for the period 2016-2019, with details: (a) financial performance of PT. Adhi Karya Tbk in the 2016-2019 period, showed that the company always received the title of Unhealthy BBB Category; (b) financial performance of PT. Housing Development Tbk in the 2016-2019 period, showed that the company received the title of Healthy Category A in 2016-2018, and received the title of Healthy Category of AA in 2019. (c) financial performance of PT. Waskita Karya Tbk in the 2016-2019 period, showed that the company received the title Healthy Category A in 2016-2018, and received the title of Unhealthy Category BB in 2019. And (d) financial performance of PT. Wijaya Tbk in the 2016-2019 period, showed that the company always received the title of Unhealthy BBB Category. (e) The result of this research signal that financial performance there influence of firm value